Reevaluation of the virulence phenotype of the inv yadA double mutants of Yersinia pseudotuberculosis. - Han, Y W (1997)
Yersinia pseudotuberculosis and Yersinia enterocolitica are closely related human pathogens causing gastroenteritis. Invasin and YadA are two of the most extensively studied virulence factors of the Yersinia genus. Invasin is the primary invasion factor encoded by the inv gene on the chromosome and is required for the penetration of the epithelial cells. YadA is encoded by the yadA gene on the 70-kb virulence plasmid and has multiple functions. Previous studies indicate that an inv yadA double mutant of Y. enterocolitica is avirulent while an inv yadA mutant of Y. pseudotuberculosis is hypervirulent. In this study, we investigated this unexpected difference. New constructs of the inv yadA mutants of Y. pseudotuberculosis were made and tested in mice. These new constructs were not hypervirulent; rather, they maintained the same virulence as the wild-type strain. Further examination of the inv mutant used for the previous study revealed that it carries an aberrant inv phenotype and has an altered outer membrane profile and an altered colony morphology. Therefore, the mutants used previously were not isogenic to the parental wild-type strain, which may in part account for the difference in the results obtained.